Frailty related all-cause mortality or hospital readmission among adults aged 65 and older with stage-B heart failure inpatients - Zheng, Pei-Pei; Yao, Si-Min; He, Wei; Wan, Yu-Hao; Wang, Hua; Yang, Jie-Fu (BMC geriatrics, 2021)
Frailty increases the adverse outcomes of clinical heart failure; however, the relationship between frailty and stage-B heart failure (SBHF) remains unknown. We aimed to explore the epidemiology and predictive value of frailty in older adults with SBHF. A prospective cohort of SBHF inpatients aged 65 years or older who were hospitalized between September 2018 and February 2019 and were followed up for 6 months were included. SBHF was defined as systolic abnormality, structural abnormality (left ventricular enlargement, left ventricular hypertrophy, wall motion abnormalities, valvular heart disease), or prior myocardial infarction. Frailty was assessed by the Fried frailty phenotype. Multivariable Cox proportional hazards regression was used to explore the independent risk and prognostic factors. Data of 443 participants (age: 76.1 ± 6.79 years, LVEF: 62.8 ± 4.92%, men: 225 [50.8%], frailty: 109 [24.6%]) were analyzed. During the 6-month follow-up, 83 (18.7%) older SBHF inpatients experienced all-cause mortality or readmission, and 29 (6.5%) of them developed clinical HF. Frail individuals had a 1.78-fold (95%CI: 1.02-3.10, P = 0.041) higher risk of 6-month mortality or readmission and a 2.83-fold (95%CI 1.24-6.47, P = 0.014) higher risk of developing clinical HF, independent of age, sex, left ventricular ejection fraction, and N-terminal pro-B-type natriuretic peptide level. Frailty is common in older SBHF inpatients and should be considered to help identify individuals with an increased risk of mortality or readmission, and developing clinical HF. ChiCTR1800017204 .